Positive and negative impacts of electrical infrastructure on animal biodiversity: A systematic review - Adam J. Bennett; David M. Watson; Maggie J. Watson (Oecologia, 2025)
Electrical infrastructure networks are predicted to greatly expand in response to the expected 48% increase in global energy demand by 2040. While assessments of electrical infrastructure are abundant, mixed effects on animal diversity have been reported, warranting further evaluation to determine true effects. We conducted a systematic literature review covering individual, population, and community-level assessments to determine the impacts posed to animal biodiversity by electrical infrastructure and the measures to reduce impacts. Our results show that the literature around electrical infrastructure and animal biodiversity has grown exponentially since the start of the millennium and is biased towards birds and mammals in economically developed countries. We found the majority of reported impacts were negative, occurring primarily through barrier effects (collision) and use of linear features as a resource (electrocution), causing significant population impacts in select species. However, we also found that electrical infrastructure provided positive effects (increased habitat provisioning) to certain taxonomic groups (e.g. corvids, storks), which suggests the potential to encourage conservation efforts using appropriate mitigation on electrical infrastructure. We found the majority of current literature detailed mitigation measures focused on reducing collisions through line (51%) and tower alterations (30%), but often omitted the impacts of EMF, noise, and UV, indicating significant knowledge gaps. On a wider scale, we found that mortality from electrical infrastructure ranked lower than building collisions and predation from feral cats, but remained higher than other anthropogenic energy sources, indicating the potential to cause significant impacts to large-bodied bird species if not addressed.